Application of bio-stimulator biocomplex 900 in producing tomato (Lycopersicon Essculentum Mill.) seedling - Đurić Milena; Mladenović Jelena; Pavlović Radoš; Zdravković Jasmina (Acta Agriculturae Serbica, 2014)
Applications of bio-stimulant Biocomplex 900 was studied in this paper in the production of tomato (Lycopersicon Essculentum Mill) seedling and the hybrid Belle was used. Indicators of growth and development were studied: mass of fresh root matter, stem and leaves, leaf area and the content of photosynthetic parameters in the leaf. A natural bio-stimulator was used in these studies as the ecological preparation, since it contains the seaweed Ascophyllum nodosum with high content of alginic acids, micro elements and amino acids. The application of this bio-stimulant showed very positive impact, compared to the control (untreated) variant and increased the values of almost all investigated parameters.